Statical excitations of DNA macromolecule with heterogenous conformation - Kanevska, P. P.; Volkov, S. N. (Biophysical Bulletin, 2018)
The model has supposed for structural mobility of DNA macromolecule in heteronomic conformation with characteristic coexistence of different sugar froms (C3’ endo, C2’ endo) in a pair of nucleotides. Double stranded structure conformational transition with simultaneous change of sugar conformation in a pair has considered for heteronomic DNA. System nonlinearity was taken into account by the form of potential function of transition C3 ’-C2’ in sugars and by correlation of transition with macromolecule deformation as well. It has been established that under transition monomer displacement is described by conformational soliton which cause macroscopic deformation of the macromolecule. Comparison of data obtained with outcomes of experoment let us assert that observed conformational excitements may be realized in DNA TATA-box.